2021
DOI: 10.1002/anie.202101766
|View full text |Cite
|
Sign up to set email alerts
|

Collective Asymmetric Total Synthesis of C‐11 Oxygenated Cephalotaxus Alkaloids

Abstract: While numerous studies pertaining to the total synthesis of Cephalotaxus alkaloids have been reported, only two strategies have been reported to date for the successful synthesis of the C-11 oxygenated subset, due to the additional synthetic challenge posed by the remote C-11 stereocenter. Herein, we report the collective asymmetric total synthesis of C-11 oxygenated Cephalotaxus alkaloids using achiral proline both as as tarting material and as the only chirality source.A tetracyclic advanced intermediate was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Only two strategies for the synthesis of 18 were reported by Fuchs [35] and Stoltz, [36] until Kim's synthesis reported in 2021. [59] Kim and coworkers applied their diastereoselective N-allylation/[2,3]-Stevens rearrangement protocol with the concept of C to N to C chirality transfer [57,58] As shown in Scheme 25, the synthesis commenced with the preparation of bicyclic 146, which employed Lewis acidpromoted cyclization of 148, which in turn can be readily prepared from l-proline. They obtained (S)-146 as the major stereoisomer, and their computational and experimental studies revealed (S)-146 to be a thermodynamically stable isomer.…”
Section: Kim's Collective Synthesis Of C11 Oxygenated Cephalotaxine-t...mentioning
confidence: 99%
See 2 more Smart Citations
“…Only two strategies for the synthesis of 18 were reported by Fuchs [35] and Stoltz, [36] until Kim's synthesis reported in 2021. [59] Kim and coworkers applied their diastereoselective N-allylation/[2,3]-Stevens rearrangement protocol with the concept of C to N to C chirality transfer [57,58] As shown in Scheme 25, the synthesis commenced with the preparation of bicyclic 146, which employed Lewis acidpromoted cyclization of 148, which in turn can be readily prepared from l-proline. They obtained (S)-146 as the major stereoisomer, and their computational and experimental studies revealed (S)-146 to be a thermodynamically stable isomer.…”
Section: Kim's Collective Synthesis Of C11 Oxygenated Cephalotaxine-t...mentioning
confidence: 99%
“…The synthesis of these congeners requires control of the C11 remote stereocenter, rendering them challenging targets for chemical synthesis. Only two strategies for the synthesis of 18 were reported by Fuchs [35] and Stoltz, [36] until Kim's synthesis reported in 2021 [59] . Kim and co‐workers applied their diastereoselective N ‐allylation/[2,3]‐Stevens rearrangement protocol with the concept of C to N to C chirality transfer [57,58] to the synthesis of diverse C11 oxygenated cephalotaxine‐type alkaloids.…”
Section: Asymmetric Synthesis Of Cephalotaxine‐type Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported that AOI involved the Friedel–Crafts reaction en route to the total synthesis of Cephalotaxus alkaloids (Figure f) . For the formation of the AOI intermediate B , O -acyl hemiacetal A was treated with a Brønsted acid.…”
mentioning
confidence: 99%
“…6 We recently reported that AOI involved the Friedel−Crafts reaction en route to the total synthesis of Cephalotaxus alkaloids (Figure 1f). 7 For the formation of the AOI intermediate B, O-acyl hemiacetal A was treated with a Brønsted acid. This transformation is analogous, in part, to the most widely applied method for the formation of Nacyliminium ions from N-acyl hemiaminal ether.…”
mentioning
confidence: 99%